Violência sexual contra crianças e adolescentes na região sul do Brasil: estudo ecológico - Cardin, Angela Gisele (2024)
This research addresses sexual violence against children and adolescents in the Southern region of Brazil, with a special focus on the border area of the Southern Arc. Sexual violence is recognized as a social and public health issue, with serious physical, social, and emotional consequences. The overall objective of the study was to analyze the incidence of sexual violence against children and adolescents between 2017 and 2022 in the Southern states of Brazil, with an emphasis on the relationship with the border area. Using data from the Notification Injury Information System (SINAN) of DATASUS, a space-time analysis was conducted covering the period from January 2017 to December 2022. Crude and standardized incidence rates were calculated and analyzed using statistical tests (t-Student and ANOVA) for group comparisons. Subsequently, spatial scan statistics were performed using SaTScan™ to identify risk clusters. Thematic maps representing the incidence rates of sexual violence and spatial risk clusters were created using QGIS software version 3.28.2. Regarding temporal .analysis, the Box-Jenkins methodology (ARIMA) was applied for time series forecasting. The .results revealed that over 6 years, 39,751 children and adolescents were victims of sexual violence in the three Southern states of Brazil, with Paraná leading in the number of cases, followed by Rio Grande do Sul and Santa Catarina. In all three states, there was an annual increase in cases until 2019, followed by a decline in 2020, the year of the pandemic's onset, and a return to growth in 2021. Both crude and standardized rates also showed a significant increase when compared between the pre-Covid-19 pandemic period (2017 to 2019) and the pandemic period (2020 to 2022), indicating disparities among different evaluated variables (states, situation regarding the border area, and gender). Gender analysis revealed that females were more affected, representing most cases. Regional investigation indicated that most cases .occurred in municipalities located outside the border area (82.63%); however, when analyzing the average rates of sexual violence, the highest rates were found in the border area municipalities. Crude and standardized incidence rates indicated a trend of increase over time, with significant differences between states and periods. Spatial analysis identified 23 clusters of sexual violence, highlighting areas with higher relative risk, with this indicator varying from 1.67 (95% CI = 1.39; 1.98) in Prudentópolis (PR) to 5.37 (95% CI = 3.94; 7.55) in Ibirama (RS). Forecasts indicate a trend of increasing sexual violence in the coming years, with variations between states. These results contribute to expanding the understanding and visibility of sexual violence and underscore the urgency of effective policies and interventions to combat sexual violence against children and adolescents in the Southern region. It is hoped that the generated information will support the development of more effective prevention and protection policies, considering the specificities of this region.